2017
DOI: 10.1021/acsnano.6b07661
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Doping in Hydrogenated Single Layered Molybdenum Disulfide

Abstract: Structural defects in the molybdenum disulfide (MoS) monolayer are widely known for strongly altering its properties. Therefore, a deep understanding of these structural defects and how they affect MoS electronic properties is of fundamental importance. Here, we report on the incorporation of atomic hydrogen in monolayered MoS to tune its structural defects. We demonstrate that the electronic properties of single layer MoS can be tuned from the intrinsic electron (n) to hole (p) doping via controlled exposure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
103
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 59 publications
8
103
1
Order By: Relevance
“…The uncertainty in Eg is the results of the lateral position variations. The relative position of EF with respect to the band edges reveals n-type doping for our samples which can be attributed to intrinsic point defects such as vacancies and/or lattice antisites, responsible for n-doping in other 2D materials [33][34][35] . The LDOS of the InSe is very sharp at the top of the valence band; near the conduction band minimum (within the range of 1.0 -1.3 eV) it is constant.…”
mentioning
confidence: 79%
“…The uncertainty in Eg is the results of the lateral position variations. The relative position of EF with respect to the band edges reveals n-type doping for our samples which can be attributed to intrinsic point defects such as vacancies and/or lattice antisites, responsible for n-doping in other 2D materials [33][34][35] . The LDOS of the InSe is very sharp at the top of the valence band; near the conduction band minimum (within the range of 1.0 -1.3 eV) it is constant.…”
mentioning
confidence: 79%
“…However, these strategies often become challenging in the monolayer limit where substitutional doping often leads to undesired out‐of‐plane defects and unstable phases with loss of advantageous properties . An alternate and highly successful strategy available to monolayer 2D materials is chemical functionalization of the van der Waals (vdW) surface . For example, exposing graphene to xenon difluoride (XeF 2 ) gas or low energy hydrogen (H) plasma, respectively, leads to fluorinated graphene (FG) or hydrogenated graphene (HG) wherein the chemisorption of foreign atoms transforms the carbon bonds from semimetallic sp 2 hybridization into insulating sp 3 hybridization .…”
mentioning
confidence: 99%
“…It is evident from the literature available on the HER on MoS 2 ‐based materials that creating tunable active defects and reducing overpotential of this reaction remain major challenges of the current research. To achieve this, various strategies are invented to improve certain physical parameters such as enhancing the density of active sites, increasing intrinsic electrical conductivity, promotion of electron transport rate, reduction of intrinsic recombination centers, etc . It has been suggested that the hybridization of MoS 2 with other nanomaterials would improve its performance with respect to the various aforementioned parameters.…”
Section: Applications Of Mos2 For Energy Conversion and Storagementioning
confidence: 99%